Beneath dark waters [large type] - Rose, Karen, 1964- (Rose, Karen, 1964- New Orleans novels, 2024)
"Public prosecutor J.P. "Kaj" Cardozo has only lived in New Orleans for six months, and he's already working on a high-profile celebrity sexual assault case that's made headlines all over the country. But when his son becomes the target of a kidnapping attempt as a threat to Kaj, he is desperate to keep him safe and turns to a private investigative firm famous for their protection services. A veteran Marine, Val Sorensen is glad to have found a new career with Broussard Investigations. Her latest assignment as the bodyguard to ten-year-old Elijah Cardozo reminds her why -- Val is a kick-ass guardian with a tender heart. Through her duties, Val grows fond of the boy -- and his handsome father. But when the high-stakes investigation reveals an explosive network of crime through a revived drug gang, lingering deep-seated corruption in the NOPD, and a group of murderers-for-hire targeting Kaj, Elijah, and his star client, they're all left scrambling for safety . . ."--